Konflik Peran Penatua dan Diaken: Implikasi Terhadap Efektivitas Pelayanan Pastoral di Gereja - Agnes Raintung; Meily M. Wagiu; Riandli Saliareng; Sindy Poluan; Renaldy V. Somba (Institut Agama Kristen Negeri Palangka Raya, 2024)
This research examines the conflict of roles and responsibilities between elders and deacons in pastoral service within the church. Utilizing a qualitative method, particularly in-depth interviews, the study not only evaluates the dynamics of the relationship between both positions but also identifies its impact on the effectiveness of pastoral services. The research findings highlight differences in perception, role conflicts, and discrepancies in responsibilities between the two roles. This conflict manifests through a gap between positive perceptions within the church and less positive interactions outside worship, creating a negative atmosphere detrimental to the participation of the congregation. Root causes of the conflict, such as individual negligence and the desire for personal recognition, are also identified. Its implications are felt in the effectiveness of services, affecting unity and spiritual growth within the congregation. The study emphasizes the importance of collaboration in pastoral services and presents solutions for consideration. The crucial role of church leadership in addressing conflicts and creating an environment supportive of unity is also underscored. In conclusion, this research details the conflict between elders and deacons, emphasizing collaborative solutions to enhance the effectiveness of pastoral services within the church.